Applying Finite Control Set - Model Predictive Control for Multilevel Modular Converter (MMC) - Tran, Hung Cuong; Tran, Trong Minh; Pham, Viet Phuong (Old Journal, 2019)
The complex process of computation of Model Predictive Control (MPC) method for the Multilevel Multilevel Control (MMC) is the main issue to overcome to reduce the computation, signal processing of the controller. This paper proposes Finite Control Set - Model Predictive Control (FCS-MPC) to minimize the computations in the MMC converter. When applying FCS-MPC for the MMC for each sampling cycle, the best switching state will be selected to generate sinusoidal alternating current, the capacitor voltages of all phases are balanced, thus limit the loop current in MMC circuit. This method will minimize the signal delay and switching frequency of the converter. This is the indirect model forecasting method to overcome the total harmonic distortion of current and voltage at the lowest level. This method overcomes the restriction when apply MMC converter in three-phase mode with high power and voltage. Simulation for MPC method on three-phase MMC converter in Matlab-Simulink has proven the advantages of the converter when applying predictive control algorithms.